Intercalation and controlled release of 2,4-dichlorophenoxyacetic acid using rhombohedral [LiAl2(OH)(6)]Cl center dot xH(2)O - Ragavan, A; Khan, A; O'Hare, D (2006)
2,4-Dichlorophenoxyacetic acid (2,4-D) has been fully intercalated into the rhombohedral polymorph of [LiAl2(OH)6]Cl·xH2O ([rhom-Li-Al] LDH) by an ion exchange method. The controlled release of 2,4-D from the interlamellar spaces of [rhom-Li-Al] LDH has been studied in a phosphate buffer, natural rainwater and deionised water. In buffer solution and rainwater, the intercalated herbicide is exchanged for anions in solution. In contrast, in deionised water the herbicide is released as part of the Li+/herbicide ion pair, leading to the formation of Al(OH)3 and the solvated ions. © 2006 Elsevier Ltd. All rights reserved.